Toxicopathological effects of lead acetate on the brain of male mice: Bassim M. Jwad ¹ and Al-Wan. M. J. - Jwad, Bassim M. (The Iraqi Journal of Veterinary Medicine, 2012)
The aim of the present study is to determine the influence of different doses of lead acetate on the central nerves system. 25 Swiss strain white mice were used, each weighing about 30 –32 g, divided into three groups, first group (n=10) treated with 0.5 ml. contain 150 mg/kg/body weight lead acetate via stomach tube daily for 40 days, second group (n=10) treated with 0.5 ml. contain 300 mg/kg/body weight lead acetate via stomach tube daily for 40 days. While the third group (n=5) served as control and were given mammalian physiological saline. Clinical signs were reported during the course of the study, then at day 40 post treatment , all animal were sacrificed and post mortem examination was done and any gross lesions were reported, then the pieces of brain was fixed in 10% formalin for 72 hours .The pathological results showed congestion of cerebellum and cerebrum of both treated group but the 2nd group was more sensitive. Histopathological examination of 1st group expressed moderate pathological lesions, characterized by extracellular edema around neuron cells and Virchow Robbin space , as well as proliferation of astrocyets in the white matter , also central chromatolysis of neurons and Nissle granules with homogenous pink their cytoplasm in 1st G. while in 2nd G the main lesions characterized by severe congestion of blood vessels with inflammatory cells infiltration in the lumen of arachnoids' space and brain parenchyma as well as hemorrhage with aggregation of microglia in the wall of blood vessels which characterized by round shape and clear cytoplasm (microgliosis). Also severe neuron degeneration, with Alzheimer's type-II astrocyets are reported in other animals characterized by pairs observed surrounded by clear space. And there is no clear pathological lesion in control group.In conclusion the present study investigated that the lead acetate affected on the brain tissue, and the degree of influence depended on the concentration of the toxic dose.